(untitled) (Research, Society and Development, 2021)
This study aimed to describe the prevalence of healthy lifestyles and examine its association to the combined effects of race and educational level in Brazil. Cross-sectional study. Data were obtained from the 2013 National Health Survey. Race was categorized as white, brown, or black, and educational level as low, medium, or high. To assess the combined effects of race and educational level, a combined variable was created. Healthy lifestyle factors were: non current smoker; non risk use of alcohol; daily consumption of fruit, and vegetables and being active. Lifestyle status was categorized as less healthy or healthier. Of the 59,249 participants, 18.4% of the whites and 6.8% of blacks reported higher education, respectively. Healthy lifestyle status differed by race and educational level. The prevalence of 3 or more parameters were higher than 80% among individuals with high educational levels, regardless of race. The association of healthy lifestyle status with the combined effects of both race and educational levels remained significant after adjustments, except in blacks and browns with high educational levels. Education may be one of an important structural determinant of health status in Brazil, especially among blacks and browns. Investments in education can be helpfull to reduce racial inequalities.